KAJIAN INTEGRASI MATEMATIKA DAN ISLAM: RUMUS FUNGSI MATEMATIKA SEDEKAH DALAM AL-QURAN - Annisaul Qoyyimah; Moh. Atikurrahman; Maswar Maswar (LP2M Universitas Ibrahimy, 2025)
This study employs a qualitative research approach, utilizing a library research method and interdisciplinary conceptual analysis, to explore the meaning of charity (Sedekah) in the Al-Qur'an and formulate a conceptual model that represents the principle of reward multiplication. Primary data are derived from Al-Qur'an verses and hadiths, particularly QS. Al-Baqarah: 261 and QS. Al-An'am: 160. Secondary data are obtained from classical and contemporary tafsir, scientific journals, and relevant literature in Islamic economics, mathematics education, and the integration of science and religion. The analysis was conducted through thematic interpretation and Islamic hermeneutics, followed by the conceptual formulation of reward multiplication using logical mathematical approaches through functional equations. This approach aims to illustrate how a single act of good deed, particularly charity, from an Islamic perspective, can yield multiplied rewards in a rational and structured manner. The findings suggest that charity holds a broad and profound meaning, occupying a significant position in Islamic teachings as a social act that promises multiple rewards. These results contribute to a more systematic and rational understanding of Islamic teachings, enriching scientific and economic perspectives on the practice of charity in contemporary contexts.